Analisis Perkembangan Pasar Modal Indonesia pada Era Digital - Ika Wahyu Indriani Ningsih; Nazwa Akhiela Salsabila Batubara; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid advancement of digital technology has significantly transformed the capital market industry in Indonesia. Digitalization has enabled easier access to investment services through online trading platforms, mobile applications, and real-time information systems. As one of the non-bank financial institutions, the capital market plays a crucial role in facilitating the flow of funds from investors to companies in need of capital. This article aims to analyze the development of the Indonesian capital market in the digital era, including the opportunities, benefits, and challenges arising from technological innovation. The study employs a descriptive qualitative approach based on literature review from academic journals, official reports, and relevant regulations. The findings indicate that digital transformation has increased investor participation, particularly among younger generations, improved transaction efficiency, and enhanced market transparency. However, challenges such as cybersecurity risks, low financial literacy, and the spread of misleading information remain significant concerns. Therefore, collaboration among regulators, market institutions, and investors is essential to ensure sustainable growth and maintain public confidence in the capital market. The digital era presents substantial opportunities for the Indonesian capital market to become more inclusive, efficient, and competitive in supporting national economic development.